Comprehensive renewable energy - Sayigh, A. A. M., 1939- (Elsevier, 2012)
Comprehensive Renewable Energy is the only multi-volume reference work of its type at a time when renewable energy sources are seen increasingly as realistic alternatives to fossil fuels. As the majority of information published for the target audience is currently available via a wide range of journals, seeking relevant information (be that experimental, theoretical, and computational aspects of either a fundamental or applied nature) can be a time-consuming and complicated process. Comprehensive Renewable Energy is arranged according to the most important themes in the field (photovoltaic t.